POLITENESS STRATEGIES USED BY STUDENTS IN CLASSROOM INTERACTION - Muhamad Luthfi (Institut Pendidikan Indonesia Garut, 2022)
In education, such as classroom teaching and learning, politeness is very important. Students communicate with the teacher during the teaching and learning process using various sayings that demonstrate politeness strategies. Considering politeness consists of methods to create appropriate politeness in communication between students and teachers. But when students use politeness strategies in giving feedback on the teacher's response, not all students can know a good speech. Therefore, this study was conducted to determine the politeness strategies used by students and teachers for classroom interaction. There are four politeness strategies based on Brown and Levinson's theory. There are bald on record, off record, positive politeness, and negative politeness. Researcher use qualitative descriptive methods to describe the results. The participants of this study were students and teachers in English classes. Researcher used two research instruments, namely interviews and observations. The Data will be analyzed by reading, analyzing, interpreting, and inferring. The results showed that the most dominant student strategy is positive politeness. Thus, this study is expected to contribute to students choosing the suitability of politeness strategies when classed.Â